On the Potential Role of the Antioxidant Couple Vitamin E/Selenium Taken by the Oral Route in Skin and Hair Health - Joël Pincemail; Smail Meziane (MDPI AG, 2022)
The relationship between oxidative stress and skin aging/disorders is well established. Many topical and oral antioxidants (vitamins C and E, carotenoids, polyphenols) have been proposed to protect the skin against the deleterious effect induced by increased reactive oxygen species production, particularly in the context of sun exposure. In this review, we focused on the combination of vitamin E and selenium taken in supplements since both molecules act in synergy either by non-enzymatic and enzymatic pathways to eliminate skin lipids peroxides, which are strongly implicated in skin and hair disorders.